College mathematics for everyday life : a college level liberal arts mathematics text - Inigo, Maxie; Jameson, Jennifer; Kozak, Kathryn; Lanzetta, Maya; Sonier, Kim; BC Open Textbook Project; BCcampus ([Publisher not identified], 2019)
"This text was written for a college-level liberal arts math class. It addresses math concepts that most people will encourter as part of their everyday life, including statistics, probablility, growth, finance, graph theory, voting systems, fair division, apportionment, and geometric symmetry and the golden ratio. Each chapter includes a set of homework questions for practice"--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
"Sponsored by: Coconino Community College".
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed on September 18, 2019).
Keywords: Mathematics; Social sciences -- Mathematics; Electronic books